Mouse Model of Loeys–Dietz Syndrome Shows Elevated Susceptibility to Periodontitis via Alterations in Transforming Growth Factor-Beta Signaling - Yamada, Satoru; Tsushima, Kenichiro; Kinoshita, Masaki; Sakashita, Hiromi; Kajikawa, Tetsuhiro; Fujihara, Chiharu; Yuan, Hang; Suzuki, Shigeki; Morisaki, Takayuki; Murakami, Shinya (Frontiers in Physiology, 2021)
Loeys–Dietz syndrome (LDS) is a syndromic connective tissue disorder caused by a heterozygous missense mutation in genes that encode transforming growth factor (TGF)-β receptor (TGFBR) 1 and 2. We encountered a patient with LDS, who had severe periodontal tissue destruction indicative of aggressive periodontitis. The patient had a missense mutation in the glycine and serine-rich domain of TGFBR1 exon 3. This G-to-T mutation at base 563 converted glycine to valine. We established an LDS model knock-in mouse that recapitulated the LDS phenotype. Homozygosity of the mutation caused embryonic lethality and heterozygous knock-in mice showed distorted and ruptured elastic fibers in the aorta at 24 weeks of age and died earlier than wildtype (WT) mice. We stimulated mouse embryonic fibroblasts (MEFs) from the knock-in mouse with TGF-β and examined their responses. The knock-in MEFs showed downregulated Serpine 1 mRNA expression and phosphorylation of Smad2 to TGF-β compared with WT MEFs. To clarify the influence of TGF-β signaling abnormalities on the pathogenesis or progression of periodontitis, we performed pathomolecular analysis of the knock-in mouse. There were no structural differences in periodontal tissues between WT and LDS model mice at 6 or 24 weeks of age. Micro-computed tomography revealed no significant difference in alveolar bone resorption between WT and knock-in mice at 6 or 24 weeks of age. However, TGF-β-related gene expression was increased significantly in periodontal tissues of the knock-in mouse compared with WT mice. Next, we assessed a mouse periodontitis model in which periodontal bone loss was induced by oral inoculation with the bacterial strain Porphyromonas gingivalis W83. After inoculation, we collected alveolar bone and carried out morphometric analysis. P. gingivalis-induced alveolar bone loss was significantly greater in LDS model mice than in WT mice. Peritoneal macrophages isolated from Tgfbr1G188V/+ mice showed upregulation of inflammatory cytokine mRNA expression induced by P. gingivalis lipopolysaccharide compared with WT macrophages. In this study, we established an LDS mouse model and demonstrated that LDS model mice had elevated susceptibility to P. gingivalis-induced periodontitis, probably through TGF-β signal dysfunction. This suggests that TGF-β signaling abnormalities accelerate the pathogenesis or progression of periodontitis.